AETA 2015: Recent Advances in Electrical Engineering and Related Sciences - Duy, Vo Hoang; Dao, Tran Trong; Zelinka, Ivan.; Choi, Hyeung-Sik.; Chadli, Mohammed; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This proceeding book consists of 10 topical areas of selected papers like: telecommunication, power systems, robotics, control system, renewable energy, power electronics, computer science and more. All selected papers represent interesting ideas and state of the art overview. Readers will find interesting papers of those areas about design and implement of dynamic positioning control system for USV, scheduling problems, motor control, backtracking search algorithm for distribution network and others. All selected papers represent interesting ideas and state of art overview. The proceeding book will also be a resource and material for practitioners who want to apply discussed problems to solve real-life problems in their challenging applications. It is also devoted to the studies of common and related subjects in intensive research fields of modern electric, electronic and related technologies. For these reasons, we believe that this proceeding book will be useful for scientists and engineers working in the above-mentioned fields of research applications. .
Keynote -- Telecommunication -- Computer Science -- Power System Paper -- Power Electronics -- Materials -- Motor Control -- Control System Paper -- Robotics -- Mechanical -- Computational Mechanics.
Keywords: Electronics; Mechatronics; Telecommunication; Control engineering; Electronics and Microelectronics, Instrumentation; Mechatronics; Communications Engineering, Networks; Control and Systems Theory